Homosexuality what about McBride ? - CRM Educational Films (Del Mar, Calif. : CRM/McGraw-Hill Films, 1974)
The video is on'homosexuality' as a sensitive and difficult topic for young people to discuss; by showing how two boys react to the suggestion that one of their friends is homosexual
Keywords: Homosexuality -- United States; Gays -- United States -- Social conditions